Analisis Penerapan Rantai Nilai Halal (Studi Pada UPTD Rumah Potong Hewan Dinas Pertanian Dan Ketahanan Pangan Kota Jambi) - Andika Afrilia Setiawan; Ridhwan .; Heni Pratiwi (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the implementation of the halal Value Chain at the UPTD Slaughterhouse of the Department of Agriculture and Food Security of Jambi City, which has an important role in providing halal meat for the Muslim majority community in Jambi City. The halal Value Chain is a series of production activities that guarantee the halalness of products, involving authorized institutions in supervision, management, testing, and policy determination, evaluation, and control of the production, distribution, and consumption processes. This study uses a qualitative method with data collection techniques through direct observation, in-depth interviews, and analysis of related documents. To achieve the research objectives, a SWOT analysis is used as a tool for formulating an effective halal Value Chain implementation strategy, taking into account the strengths, weaknesses, opportunities, and threats faced by the UPTD Slaughterhouse. The results of the study indicate that the implementation of the halal Value Chain at the UPTD Slaughterhouse in Jambi City has been carried out systematically in accordance with the principles of halalan thayyiban and the Safe, Healthy, Whole, and Halal (ASUH) standards. Supporting factors include halal certification, accreditation of the Veterinary Control Number (NKV), and the presence of Halal Slaughterers (JULEHA). The main challenges include limited human resources (HR), the absence of an internal laboratory, and lack of distribution supervision. Recommended strategies include strengthening cross-agency collaboration, increasing training, and improving infrastructure and supervision systems to ensure sustainability and increase trust in halal products.